Praktik pemberian makanan pendamping ASI (MP-ASI) bukan faktor risiko kejadian stunting pada anak usia 6-23 bulan - Hildagardis M.E Nai; I Made Alit Gunawan; Esti Nurwanti (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2014)
ABSTRACTBackground: Stunting reflects a process of failure to reach linear growth potential as a result of suboptimal health or nutrition conditions. One of causal factors of stunting is inadequate of quality and quantity of complementary foods.Objectives: To identify complementary feeding practices such as introduction age of complementary foods, dietary diversity, and meal frequency as risk factors of stunting among children aged 6-23 months in Sedayu Subdistrict, Bantul, Yogyakarta.Methods: Study design was case-control with ratio (1:1). The study used both quantitative methods as well as case control design and qualitative through interview. Cases were children aged 6-23 months who had length for age z-score <-2SD. Controls were children aged 6-23 months who had length for age z-score ≥-2SD who live adjacent to the case. Data were analyzed by using univariable (descriptive), bivariable (chi-square test), and multivariable analysis (multiple logistic regression).Results: The result of bivariate analysis showed that introduction age of complementary foods (OR=1.07), dietary diversity (OR=1.17), and meal frequency (OR=1.69) were not risk factors of stunting. However, compared with high dietary diversity score, low dietary diversity score (≤2, 3, 4 food groups) associated with increased odds of being stunted among children aged 6-23 months (OR=2.24, 95% CI:1.00-5.01, OR=1.82, 95% CI:0.96-3.45, OR=1.66, 95% CI:0.81-3.46 respectively). The result of multivariate analysis showed that mother’s height (OR=1.86) and story of low birth weight (OR=3.23) were risk factors of stunting.Conclusions: Complementary feeding practices such as age introduction of complementary foods, dietary diversity, and meal frequency were not risk factors of stunting among children aged 6-23 months. Mother’s height and story of low birth weight were risk factors of stunting among children aged 6-23 months.KEYWORDS: stunting, nutritional intake, nutritional status, complementary foods ABSTRAKLatar belakang: Stunting merefleksikan kegagalan proses mencapai potensi pertumbuhan linear sebagai akibat dari kondisi kesehatan dan gizi yang tidak optimal. Salah satu penyebab kejadian stunting adalah kuantitas dan kualitas MP-ASI yang rendah.Tujuan: Untuk mengidentifikasi risiko praktik pemberian MP-ASI seperti usia pengenalan MP-ASI, keragaman MP-ASI, dan frekuensi MP-ASI dengan kejadian stunting pada anak usia 6-23 bulan di Kecamatan Sedayu, Bantul, Yogyakarta.Metode: Rancangan penelitian ini adalah kasus-kontrol dengan perbandingan 1:1 dan menggunakan pendekatan kuantitatif-kualitatif model concurrent embedded. Kasus adalah anak usia 6-23 bulan yang memiliki skor-z PB/U <-2SD. Kontrol adalah anak usia 6-23 bulan yang memiliki skor-z PB/U ≥-2SD yang tinggal berdekatan dengan kelompok kasus. Analisis data menggunakan analisis univariat (deskriptif), bivariat (uji chi-square) dan multivariat (uji regresi logistik berganda).Hasil: Analisis bivariat menunjukkan usia pengenalan MP-ASI (OR=1,07), keragaman MP-ASI (OR=1,17), dan frekuensi pemberian MP-ASI (OR=1,69) bukan faktor risiko kejadian stunting (p>0,05). Skor keragaman MP-ASI yang lebih rendah (kelompok makanan ≤2, 3, 4) berhubungan dengan peningkatan risiko kejadian stunting berturut-turut OR=2,24, 95% CI:1,00-5,01; OR=1,82, 95% CI:0,96-3,45; OR=1,66, 95% CI:0,81-3,46. Analisis multivariat menunjukkan faktor risiko kejadian stunting adalah tinggi badan ibu (OR=1,86) dan riwayat berat badan lahir rendah (BBLR) (OR=3,23,).Kesimpulan: Praktik pemberian MP-ASI seperti usia pengenalan, keragaman, dan frekuensi pemberian MP-ASI bukan merupakan faktor risiko kejadian stunting pada anak usia 6-23 bulan. Faktor risiko kejadian stunting pada anak usia 6-23 bulan yang bermakna adalah tinggi badan ibu dan riwayat BBLR.KATA KUNCI: stunting, asupan makan, status gizi, MP-ASI